Analytical calculation method for passive tensile damage of asphalt concrete waterproof sealing structure of ballastless track subgrade. (21st February 2022) - Cai, Degou; Chen, Peipei; Shi, Yuefeng; Yao, Jianping; Yan, Hongye; Peng, Peihuo
Highlights: A model of the elastic–viscoelastic double-layer composite beam is established. The reliability of the double-layer composite beam model is verified by test data. The mechanical response of ACWSS under temperature load is analyzed. The leading cause of passive tensile damage of ACWSS is a strain mutation. ACWSS at the expansion joint mainly bears axial tensile/compression deformation. Abstract: The theoretical development of the temperature effect of the full-section asphalt concrete waterproof sealing structure (ACWSS) of the ballastless track subgrade lags the engineering practice. In order to reveal the passive tensile damage behavior of ACWSS from the perspective of theoretical analysis, in this paper, the base plate of the ballastless track and the ACWSS is simplified into an elastic–viscoelastic double layer composite beam model. The analytical calculation method for passive tensile damage of ACWSS under temperature load is derived theoretically. The change of surface stress and strain of ACWSS with time is calculated and analyzed. The theoretical analysis and calculation results show that the variation of the surface strain, the maximum strain, and the time corresponding to the strain peak of ACWSS are consistent with the measured results. The model of the double-layer composite beam has high reliability, and the analytical calculation method of passive tensile damage is reasonable and practical. The temperature stress of ACWSS at the expansion joint of the base plate is synchronized with the temperature change, indicating that the asphalt concrete at this location is mainly subjected to axial tension (or compression). It is suggested that the structural design should be judged by comparing the number of periodic temperature loads and the allowable fatigue number of asphalt concrete, which further improves the design method and technical system of the ACWSS in China's high-speed railway. It has important theoretical and practical significance.